Public Relations Officer on Screen: An Analysis of Professional Practices of Public Relations Officers in the Industry - Brigitta Revia Sandy Fista; Yuli Nugraheni (Program Studi Ilmu Komunikasi Universitas Serang Raya, 2022)
This study attempts to dissect the tendency to depict public relations institutions in the films produced by Warner Bros and Columbia Pictures. These two production houses are listed as the companies that most often release new films in America. Characters who have profiles as public relations institutions appear in films produced by different production houses. The research will be conducted by taking film samples in the 2010-2019 period. The selection of this year's range is based on previous studies that also used content analysis to look for trends in the depiction of the public relations profession in films in the period 1990-2000 and 2000-2009. This study uses a quantitative approach with descriptive type and uses the method of content analysis. The results show that there are differences in content on the characteristics of the PR profession, the type of campaign in The Social Network and Our Brand is Crisis films. Then on the indicators of the aspect of persuasion, there are similarities from the aspect of persuasion used in the practice of the PR profession.